2021
DOI: 10.1109/jstars.2020.3047897
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Comparative Evaluation of the GPM and TRMM Precipitation Products Against Ground Precipitation Observations Over Chinese Tibetan Plateau

Abstract: This study aims to evaluate the performances of two latest released GPM-era satellite precipitation final run products (IMERG-V06B and GSMaP-V07) and one TRMM-era product (TMPA-3B42-V07) at hourly, daily and monthly scale over the TP, with special focus on the performances at different rain intensities, sub-basins, and elevations at daily scales. Besides, hourly scale evaluations were carried out for one grid box value of IMERG-V06B and GSMaP-V07 versus 15 rain gauges on the rainy season, 2019. Results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…From Figure 14a, it can be noticed that there are two blocks in the scatter plot of the POD versus elevation, and this is possibly due to the weak correlation between these two variables. Some previous studies also found that the detectability decreases with altitude for GPM in the TP [29,38]. With the increasing altitude, the percentage of snowfall in precipitation tends to increase in the UB.…”
Section: Strengths and Limitations Of The Four Precipitation Productsmentioning
confidence: 69%
See 2 more Smart Citations
“…From Figure 14a, it can be noticed that there are two blocks in the scatter plot of the POD versus elevation, and this is possibly due to the weak correlation between these two variables. Some previous studies also found that the detectability decreases with altitude for GPM in the TP [29,38]. With the increasing altitude, the percentage of snowfall in precipitation tends to increase in the UB.…”
Section: Strengths and Limitations Of The Four Precipitation Productsmentioning
confidence: 69%
“…Based on observed precipitation from TP meteorological stations, Li et at. [38] also found that there are small CC values between satellite precipitation products (TRMM and GPM) and rain gauge measurements. The complex topography; high-altitude areas covered by snow, glaciers, permafrost; and sparsely distributed precipitation gauges over UB would affect the accuracy of these precipitation products and result in a low correlation with the reference precipitation as compared with other regions in the world.…”
Section: Statistical Evaluation Of Gridded Precipitation Productsmentioning
confidence: 78%
See 1 more Smart Citation
“…Jiang et al [19] compared TRMM 3B42V6, TRMM 3B42RTV6, and CMORPH in the Laoha River basin, and indicated that the systematic deviations of the three SPPs were 21%, 67% and 81% on the daily time scale, respectively. Li et al [20] evaluated the performances of IMERG V06B, GSMaP V07 and TMPA 3B42V7, and recommend the GSMaP V07 for satellite precipitation data application within the TP. Romilly and Gebremichael [21] and Shrestha et al [22] summarized the conclusions of the former relevant studies and reveal that the quality of SPPs is related to a variety of factors.…”
Section: Introductionmentioning
confidence: 99%
“…Since the mid-1950s, the Qinghai-Tibet Plateau (TP) has witnessed signi cant temperature warming, making it vulnerable to climate change (Wang et al, 2008;Guo andWang, 2012, Gao et al, 2019). However, data scarcity has hampered signi cant research in hydrology and climate over TP (Yin et al, 2008;Maussion et al, 2014;Li et al, 2021a;Li et al, 2021b). Primarily, ground observations are used to measure precipitation; however, the coverage density is insu cient to provide adequate climate data (Geng et al, 2017;Li et al, 2021a;Wei et al, 2021).…”
Section: Introductionmentioning
confidence: 99%